Social Responsibility and Three-Dimensional Libraries: sustaining the information ‘life’ in Sri Lanka - Arulanantham, S.; Ramanan, T. (3rd International Conference on Association of Special Libraries. Manila., 2013)
This paper is based on the experiences from experiments on three-dimensional library services and aims at the extent and outcomes of such services set up in the university library, school libraries and public libraries in Jaffna District, Sri Lanka. This was an innovative service conceived by the librarian of the University of Jaffna, Sri Lanka (first author). Therefore, the paper looks into the potentiality of the services across the country, especially in war-torn areas and possibility of sustaining the reading habit of the user community. Further, it elaborates as to how this unique service could be of great importance to the entire society that was war-torn for the past three decades. In addition, the authors recommend such beneficial practice to be spread across the nation to enhance the reading habit and information seeking behavior of the people who were struck by the war and Tsunami. Further it proposes that this venture could be extended to the digital library services to bring all the library services in the country under a cooperative arrangement.
Keywords: Three-Dimensional Library; Social Responsibility; Information Services; Public Relations; Digital Library Services